Can a single molar root act as a whole tooth? - Vittorio Checchi (Wolters Kluwer Medknow Publications, 2022)
This clinical case describes the longitudinal outcome of a radisected upper molar root. The palatal root acted as an abutment and was finalized with a double-premolar-shaped metal-resin crown with two rests on the adjacent teeth. Fifteen years later, the root and its crown were still in place, with no pathologic pocket probing depth and lack of inflammation; the tooth was still in function with no signs of periodontal breakdown. This therapeutic option seemed to have been biologically respectful and maintains the possibility to provide future implant therapy.